Apakah Profitabilitas Pada Bank Umum Konvensional dapat dipengaruhi oleh NPL, BOPO, dan CR ? - Angguliyah; Musa, Rafida (Fakultas Ekonomi dan Bisnis, Universitas Islam Raden Rahmat Malang, 2024)
Research on Conventional Commercial Banks aims to explore whether financial performance can be influenced by factors such as Non-Performing Loans, Operating Costs, Operating Income, and Cash Ratio. This study was conducted on Conventional Commercial Banks listed on the Indonesia Stock Exchange in the 2019-2022 period. The research method used was descriptive quantitative, with sample selection using a purposive random sampling method, which resulted in 10 commercial banks as research subjects. Data analysis was carried out using Financial Performance Assessment, Partial Least Square and Structural Equation Modeling techniques with the help of SmartPLS-3 statistical software. The research results show that there is a direct and positive influence, namely: 1) Non-Performing Loans on Return on Assets and Return on Equity, 2) Operating Costs Operating Income on Return on Assets, Return on Equity, and Cash Ratio. On the other hand, there is a direct and negative influence, namely: 1) Operating Costs Operating Income on Non-Performing Loans, 2) Cash Ratio on Return on Assets and Return on Equity. Apart from that, the research results show that there are indirect and negative influences, such as: 1) Operational Costs Operational Income influences Return on Assets through Non-Performing Loans and Cash Ratio, 2) Operational Costs Operating Income influences Return on Equity through Non-Performing Loans and Cash Ratio Keywords: Non Performing Loans, Operational Costs Operational Income, Cash Ratio, Profitability